Zeckendorf Representations and Mixing Properties of Sequences - Mañibo, Neil (Archīum Ateneo, 2020)
We use generalised Zeckendorf representations of natural numbers to investigate mixing properties of symbolic dynamical systems. The systems we consider consist of bi-infinite sequences associated with so-called random substitutions. We focus on random substitutions associated with the Fibonacci; tribonacci and metallic mean numbers and take advantage of their respective numeration schemes.